In the mood for mood - Mortelmans, Tanja; Mortelmans, Jesse; De Mulder, Walter (Cahiers Chronos ;, 2011)
This volume is a selection of papers presented at the 7th Chronos colloquium in Antwerp (2006), which deal with the expression of modality (in a wide sense), by modal and semi-modal verbs (in Germanic and Romance languages), on the one hand, and by other markers (in languages like Turkish, Tibetan and Japanese), on the other. The Antwerp edition's special conference topic was the interaction between tense and modality, of which some of the papers collected in this volume also testify. The volume covers a wide range of languages and topics. Specific topics include: the distinction between root.